Karakteristik Siswa dengan Pelaku Attention Deficit Hyperactivity Disorder (ADHD) dan Upaya Penanganannya - Diajeng Arta Anenda; Dita Maisurah; Islahul Adila Rahma; Rahmadhani Fitri (LPPM Politeknik Pratama, 2024)
Children with Attention Deficit Hyperactivity Disorder (ADHD) are frequently encountered in everyday life, especially among school-age children to adolescents. This condition necessitates special education or services to meet their needs in optimizing individual potential and abilities. The presence of children with ADHD often poses a challenge in the context of the learning process. Understanding the characteristics of students with ADHD is key to planning more effective learning strategies. This study aims to outline the characteristics of students with ADHD in inclusive school environments. The method used is a literature review or literature study. The research results indicate that the main characteristics of students with ADHD include difficulty in focusing attention (inattention), difficulty in controlling impulses (impulsivity), and difficulty in controlling movement (hyperactivity). The conclusion of this research is that teachers in inclusive schools can gain a better understanding of the characteristics of students with ADHD, and from there can design more effective learning strategies.